3D printing from MRI Data: Harnessing strengths and minimizing weaknesses. Issue 3 (22nd November 2016) - Ripley, Beth; Levin, Dmitry; Kelil, Tatiana; Hermsen, Joshua L; Kim, Sooah; Maki, Jeffrey H; Wilson, Gregory J
Abstract : 3D printing facilitates the creation of accurate physical models of patient‐specific anatomy from medical imaging datasets. While the majority of models to date are created from computed tomography (CT) data, there is increasing interest in creating models from other datasets, such as ultrasound and magnetic resonance imaging (MRI). MRI, in particular, holds great potential for 3D printing, given its excellent tissue characterization and lack of ionizing radiation. There are, however, challenges to 3D printing from MRI data as well. Here we review the basics of 3D printing, explore the current strengths and weaknesses of printing from MRI data as they pertain to model accuracy, and discuss considerations in the design of MRI sequences for 3D printing. Finally, we explore the future of 3D printing and MRI, including creative applications and new materials. Level of Evidence: 5 J. Magn. Reson. Imaging 2017;45:635–645.